Transformasi Digital Untuk Pemasaran Online Melalui Penyuluhan - ibrahim, Helda; M.Zain, Majdah; Sulfiana, Sulfiana; Hasmirati, Hasmirati; Husain, Fahrisal; Asrib, Ahmad Rifqi Asrib (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2025)
The outreach and digital transformation activities for online marketing in Aeng Batu-Batu Village, South Sulawesi, aim to enhance the community's understanding and skills in utilizing digital technology. In the context of economic empowerment, this initiative focuses on developing the marketing of agricultural products through digital platforms, which is expected to improve the competitiveness of Micro, Small, and Medium Enterprises (MSMEs). The methods employed include lectures, discussions, and hands-on practices, involving various local stakeholders, including farmers and housewives.The results of these activities indicate an increased awareness among the community regarding agribusiness digitalization and the importance of digital literacy. With this training, it is hoped that the community can optimize local potential, increase income, and reduce reliance on conventional marketing methods. This initiative serves as an initial step in facilitating the community's adaptation to the digital era, while also supporting local economic sustainability.